Homoploid hybrid speciation in animals (2008)
Among animals, evidence for homoploid hybrid speciation (HHS, i.e . the creation of a hybrid lineage without a change in chromosome number) was limited until recently to the virgin chub, Gila seminuda , and some controversial data in support of hybrid status for the red wolf, Canis rufus . This scarcity of evidence, together with pessimistic attitudes among zoologists about the evolutionary importance of hybridisation, prompted the view that HHS is extremely rare among animals, especially as compared with plants. However, in recent years, the literature on animal HHS has expanded to include several new putative examples in butterflies, ants, flies and fishes. We argue that this evidence suggests that HHS is far more common than previously thought and use it to provide insights into some of the genetic and ecological aspects associated with this type of speciation among animals.